(untitled) (Research, Society and Development, 2022)
At the end of this review on applications of ultrasonic waves in the inactivation of microorganisms in hospital laundry effluents, the fourth type of predictive model is proposed, based on the application characteristics of the experimental plans. The number of works for the disinfection of wastewater by ultrasound waves (US) associated with other techniques or individuals has been increasing. The use of ultrasound to produce lethal effects on microorganisms is attractive because it is considered a "green" technology in that it involves sound energy and does not require additional chemicals, or a very small amount. Also, the US as a tool for water reuse processes - operates at low pressure and temperature and does not produce toxic or greenhouse gases. Hospital laundry effluents are characterized by different microorganisms, a fact that can hinder the application of conventional physical-chemical technologies. To contribute to future developments in the application of ultrasound (US), this work uses some typical US applications in the disinfection of aqueous effluents. To propose strategies for carrying out new works, comments are made regarding an approach oriented towards new advances based on the need to interrelate the variables involved in the studies, at the same time that these variables are correlated with the rate of inactivation. For this, it is discussed the predictive models and their contributions, according to the number of factors that should be involved for a better understanding of the rate of microbial inactivation.